Consumer Satisfaction as a Mediator of the Influence of Facilities, Price, and Taste on Repeat Purchase Intention at Mi Gacoan in Taman Sidoarjo. - Sandra Oktaviana; Fedianty Augustinah; Damajanti Sri Lestari; Andry Herawati; Liling Listyawati, (International Journal of Scientific Research and Management (IJSRM), 2024)
This investigation aims to fill a gap in the current literature by examining the effects of price, flavour, and facilities on repurchase intention. The assumption is that consumer satisfaction serves as a mediator, as it promotes repeat purchases. The study examines the influence of price, taste, and facilities on repurchase intention, emphasizing the importance of customer satisfaction. Data was collected through purposive sampling in order to investigate the impact of these variables and test the hypotheses, utilizing an Explanatory Research design. Data from 151 customers of Resto Mie Gacoan were analyzed using the Structural Equation Model (SEM) approach with Partial Least Squares (PLS). The results indicated that two of our proposed hypotheses were rejected: facilities did not significantly impact repurchase intention, and taste did not significantly influence customer satisfaction. Our findings also showed that customer satisfaction effectively mediates the influence of facilities, price, and taste on repurchase intention.